Identification and Functional Characterization of a Novel UDP-Glucuronosyltransferase 2A1 Splice Variant: Potential Importance in Tobacco-Related Cancer Susceptibility - Bushey, Ryan T. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
UDP-glucuronosyltransferase (UGT) 2A1 is a respiratory and aerodigestive tract-expressing phase II detoxifying enzyme that metabolizes various xenobiotics including polycyclic aromatic hydrocarbons (PAHs). In the present study, a novel exon 3 deletion splice variant was identified for UGT2A1 (UGT2A1Δexon3). As determined by reverse transcription-polymerase chain reaction (PCR), UGT2A1Δexon3 was shown to be expressed in various tissues including lung, trachea, larynx, tonsil, and colon. The ratio of UGT2A1Δexon3/wild-type UGT2A1 expression was highest in colon (0.79 ± 0.08) and lung (0.42 ± 0.12) as determined by real-time PCR; an antibody specific to UGT2A1 showed splice variant protein (UGT2A1_i2) to wild-type protein (UGT2A1_i1) ratios in the range of 0.5 to 0.9 in these tissues. Using ultra-pressure liquid chromatography, we found that homogenates prepared from UGT2A1_i2-overexpressing human embryonic kidney 293 cells exhibited no glucuronidation activity against PAHs, including benzo[a]pyrene-7,8-dihydrodiol (B[a]P-7,8-diol). An inducible in vitro system was created to determine the effect of UGT2A1_i2 expression on UGT2A1_i1 activity. Increasing UGT2A1_i2 levels resulted in a significant (p < 0.01) decrease in the UGT2A1_i1 V(max) against 1-hydroxy (OH)-pyrene, 3-OH-benzo[a]pyrene, and B[a]P-7,8-diol; no significant changes in K(M) were observed for any of the three substrates. Coimmunoprecipitation experiments suggested the formation of UGT2A1_i1 and UGT2A1_i2 hetero-oligomers and UGT2A1_i1 homo-oligomers; coexpression of UGT2A1_i1 or UGT2A1_i2 with other UGT1A or UGT2B enzymes caused no change in UGT1A or UGT2B glucuronidation activity. These data suggest that a novel UGT2A1 splice variant regulates UGT2A1-mediated glucuronidation activity via UGT2A1-specific protein-protein interactions, and expression of this variant could play an important role in the detoxification of carcinogens within target tissues for tobacco carcinogenesis.